Directed Giving: Evidence from an Inter-Household Transfer Experiment - Catia Batista; Dan Silverman; Dean Yang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
We investigate the determinants of giving in a lab-in-the-field experiment with large stakes. Study participants in urban Mozambique play dictator games where their counterpart is the closest person to them outside their household. Dictators share more with counterparts when they have the option of giving in kind (in the form of goods), compared to giving that must be in cash. Qualitative post-experiment responses suggest that this effect is driven by a desire to control how recipients use gifted resources. Standard economic determinants such as the rate of return to giving and the size of the endowment also affect giving, but the effects of even large changes in these determinants are significantly smaller than the effect of the in-kind option. Our results support theories of giving where the utility of givers depends on the composition (not just the level) of gift-recipient expenditures, and givers thus seek control over transferred resources.
Keywords: C92; C93; D01; D03; D64; O17; 330; sharing; altruism; giving; dictator game; inter-household transfers; Mozambique